(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
جمعت عينات مياه شاطئية من تسعة مواقع في منطقة مصب نهر الكبير الجنوبي خلال الفترة الزمنية الممتدة من 5/7/2004 ولغاية 29/6/2005، بغية تحديد شوارد النترات والنتريت والفوسفات والبكتريا في هذه العينات. سُجلت أعلى التراكيز لشوارد النترات والنتريت والفوسفات على مدار العام قي الموقع L/S1 (داخل مجرى النهر)، ولُحظ انخفاض قيمها مع تزايد العمق والبعد عن موقع مصب النهر باستثناء الموقعين L/S6 و L/S7 في شهري كانون أول وآذار على التوالي. من ناحية ثانية، سجل أعلى تركيز للبكتريا من النوع (fecal coli forms) على مدار العام في الموقع L/S1 ، مما يشير إلى تلوث عضوي بشري حديث، وكان انخفاضها التدريجي واضحاً مع تزايد البعد عن مصب النهر، أما البكتريا من النوع (fecal streptococcus) التي تشير إلى تلوث بشري قديم، فظهرت في جميع المواقع خلال شهري حزيران وكانون الأول، وكانت تراكيزها أكثر وضوحاً في المواقع الأقرب إلى مصب النهر. Samples of marine shore water from nine sites of estuarine-Alkabeer Aljnouby River were collected during the period 5/7/2004-29/6/2005 in order to determine their content of nitrate, nitrite, phosphate ions and bacteria. The higher concentrations of the selected ions were reported in site L/S1 (inside the river), while a depression in their concentrations was observed due to the depth and distance of the site from the river estuarine in the sites L/S6 and L/S7 in January and March respectively. The higher concentrations of bacteria (fecal coli forms) were reported during the whole year in site L/S1, which indicates to a recent anthropogenic organic pollution, whereas a stepwise decreasing in its concentrations was observed due to the distance of site from the river estuarine especially in the far sites. The bacteria (fecal streptococcus) that indicates an old anthropogenic organic pollution appears in all sites during January and June and the high concentrations were more clear in the site near the river estuarine.